The Effect Of Price, Location, And Customer Income Through Subsidized Housing Purchase Decisions At Kabupaten Jembrana, Bali - Ardana, Ketut; Rahayu, Isyana; Sudiarti, Sri; Sarmidi, Sarmidi (Management Department Universitas Islam Negeri Sumatera Utara, 2023)
Fulfillment of housing needs by the community is a basic thing that must currently be fulfilled in order to improve a better quality of life. This study was conducted with the aim of knowing the effect of price (X1), location (X2), and consumer income (X3) will affect the decision to purchase subsidized housing (Y) using multiple linear regression analysis methods, and hypothesis testing including the t test, F test, and coefficient of determination test. Data collection was carried out using the interview method with subsidized housing consumers Mulia Jaya in Jembrana Regency. The results of this study indicate that price, location, and consumer income have a positive influence on subsidized housing purchase decisions, namely 0.004 <0.05 and an f-count value of 5.786> f-table 3.245, meaning that there is a simultaneous or joint influence of price (X1), location (X2) and consumer income (X3) on the decision of consumers to purchase subsidized housing (Y). The research results from the various analyzes carried out can be used as benchmarks and references for other researchers to conduct similar research but with different places that can use this research as a reference to produce higher quality research results. Keywords: Costumer income, Location, Price, Purchase decision